Chiune Sugihara and Jan Zwartendijk: the Righteous of the World Nations. Historical Peripeteias among Soviet Structures, Jewish Refugees and Their Redeemers - Strelcovas, Simonas (Genocidas ir rezistencija, 2003)
The article is devoted to representatives of two foreign countries, to the Consul of Japan Chiune Sugihara, and to the Consul of the Netherlands in interim Jan Zwartendijk, their activities in Kaunas, in the summer 1940 and their relations with the Jewish war refugees. Both diplomats became the historical personalities recognized on the world level since due to their activities they rescued several thousands of people of Jewish origin.
Keywords: German occupation; Jews; Holocaust; jewish redeemers; Chiune Sugihara